Self-practice ringkasan (SPRing): an innovative mobile apps for self-practice / Asmahani Mahdi ... [et al.] - Mahdi, Asmahani; Bohari, Zubaidah; Abdul Talip, Abdul Hadi; Kamarudin, Nurul Lizzan; Haji Bibi, Zainon (2021)
Practice makes perfect is a proverb which tells us the importance of continuous practice or learning in order to become proficient in what we do. There is no alternate to hard work and success. As an educator, practice is the best approach to ensure all the knowledge is successfully delivered. The usage of technology such as computer, mobile phone, tablet and application are essential in the education process. In this era, the intention to ensure students engaging in the learning process become a big challenge to educators. They believed that with practice it helps student to build both their skills and memorization. Therefore, SPRing was developed to enhance the memorisation among students through effective and innovative learning approach. SPRing is specifically developed for students who are taking Executive Note-Taking (OBM200) in Diploma of Office Management and Technology. The main outcome for this subject it to ensure the students are able to master note-taking skills both in English and Bahasa Melayu. SPRing is the mobile apps focused on Bahasa Melayu writing system known as RINTAS. Ringkasan is part of RINTAS. The ability to master this skill required students to give more effort by doing exercise, to understand different rules and to memorize Ringkasan. The note-taking skills become the essential skills for office personnel. This mobile apps will help them revise Ringkasan and be efficient while performing their task. Self-practice is one of the best efforts that describes student centered learning environment. SPRing is developed due to conditions that there is no constraint for mobile phone. The use of mobile apps for learning is more sustainable compared to the traditional learning methods which include papers, pencils, and pens. A pilot study which was conducted among 15 students who currently taking this subject showed that most of them were satisfied and enjoyed using SPRing. It also revealed that most of them feel they need to have this mobile apps. In addition, it can improve the teaching quality and learning environment among new generations.